Διερεύνηση βιολογικών πληροφοριών σε σχέση με την τοξικότητα: εφαρμογή σε πρωτεϊνικά δεδομένα νανοσωματιδίων - Ρούσση, Αλεξάνδρα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ). Μονάδα Αυτόματης Ρύθμισης και Πληροφορικής, 2015)
This diploma thesis focused on the scientific area of Bioinformatics and in particular Biostatistics and its application to nanotechnology, and specifically on the data class known as protein corona of nanomaterials which is a scientific area of increasing interest. The properties of these data have been recorded by protein clustering techniques in order to predict the toxicity of nanomaterials. In this work, it is their biological information that is investigated by using gene ontology terms (Gene Ontology, GO). In particular, a series of mathematical algorithms were applied to three different proteomic data sets in order to find the data relationships, their classification and grouping based on their functional properties and the over-expression analysis of proteins in the environment they are being tested. For the analysis presented, available algorithms of the open source software Bioconductor were used in the environment of statistical programming language R. Firstly protein and gene identifiers were converted to GO biological function identifiers, in order to create GO graphs which illustrate the relationship between GO terms and hence between proteins/genes. Then, we classified genes into their functional classes and calculated their similarities. Finally, enrichment analysis was performed using different libraries to identify which proteins and therefore genes are more than usually expressed on the inlet conditions of a nanoparticle in the human organism. Our results showed that the estimated overexpressed genes which reveal the biological identity of a nanoparticle, are frequently related to cellular functions associated with toxicity. These cellular functions are: activation of complement, cell association, lipid transport, activation and response of the immune system and blood coagulation